ANALYSIS OF MORAL VALUES IN THE UPIN IPIN CARTOON FILM EPISODE 14 (TUDUNG SAJI MENGKUANG) - Ni Kadek Karmaeni (Adisam Publisher, 2025)
Cartoon films are the most popular films for children, not only children, cartoon films are also often watched by teenagers and adults. because cartoon films have a concise storyline and pictures. Not many words are used. Easy to understand and recognize. The message is usually fresher and clearer. So cartoon films are one type of animated film that is the most popular choice or show for children. One of the children's cartoon films that airs on TV is Upin & Ipin. in the Upin & Ipin film using Malay / Malaysian. But the language used is easy to understand by Indonesian children because Malaysian and Indonesian have little similarity. This study aims to analyze the cartoon film